Tuning into client needs: Matching supply and demand for the television tuner division at infineon Asia-Pacific - OTT, Holly (Institutional Knowledge at Singapore Management University, 2011)
In this case, we are introduced to the highly complex semiconductor industry, which is characterized by its well-known “boom-n-bust” cycles: periods of high demand and worldwide allocation for integrated circuits, followed by periods of low demand, excess capacity, and high stocks. The key challenges for supply chain management are described, including the volatile semiconductor market; the high cost of capital leading to “fabless” companies outsourcing wafer production and contract manufacturers for assembly; long production cycle times: up to four months for the wafer fabrication and two-three weeks for the back end assembly; and communication in a global organization. The proliferation of products, very steep product ramps and short product lifecycles add to the complexity. The television tuner market, described as a price-sensitive commodity market, is specifically challenging. The goal of the case is to develop a six-month inventory plan for three tuner products, using the information provided in the case to balance the inventory levels with the customer demand and the factory capacity utilization. Supply chain concepts covered: Rolling Forecasting Cycle Fiscal Calendar (4-4-5) Marketing View vs Operations View: striking a balance between forecasted demand (P&L) vs actual order and billings situation SCOR-based Performance Metrics (Stock Reach vs. Capacity Utilization) Consignment Stock Global organizations